2022
DOI: 10.5603/ep.a2022.0006
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 lockdown does not necessarily worsen diabetes control, in spite of lower physical activity — a systematic review

Abstract: REVIEWrupted this care, and patients with chronic diseases faced difficulties in obtaining medicine, follow-up, and monitoring of diseases status. Diabetes is a common chronic disease globally, with about 463 million people affected [7]. These diabetics need continuous care and must maintain a healthy lifestyle, such as diet and physical activity, in order to keep glucose levels within normal ranges. Failure to do so may result in another pandemic of complications, mortality, and increased burden on health sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Even the results of studies from one continent or country were various. For example, we found that in all Japanese studies, patients gained weight during the lockdown and social distancing (Da Silva et al, 2020;Munekawa et al, 2020;Kishimoto et al, 2021;Tanaka et al, 2021;Aldukhayel, 2022;Maruo et al, 2022;Takahara et al, 2022). Capaldo et al (2020) represented a decrease in PPBS (1.04%), while Caruso et al, 2021 reported an increase in PPBS (1.45%) during the lockdown and social distancing.…”
Section: First Author (Year)mentioning
confidence: 85%
“…Even the results of studies from one continent or country were various. For example, we found that in all Japanese studies, patients gained weight during the lockdown and social distancing (Da Silva et al, 2020;Munekawa et al, 2020;Kishimoto et al, 2021;Tanaka et al, 2021;Aldukhayel, 2022;Maruo et al, 2022;Takahara et al, 2022). Capaldo et al (2020) represented a decrease in PPBS (1.04%), while Caruso et al, 2021 reported an increase in PPBS (1.45%) during the lockdown and social distancing.…”
Section: First Author (Year)mentioning
confidence: 85%
“…Of 175 international systematic reviews identified in PubMed (date of search: 9 December 2022), 10 potentially relevant reviews described impact on glycaemic control,17–20 diabetic ketoacidosis21 and interventions to recover or sustain diabetes or hypertension care 22–26. Overall, improvements in glycaemic control were seen in high-income countries during the pandemic, likely reflecting a high motivation for diabetes self-management due to associations with COVID-19 outcomes, supportive care through teleconsultations, and easier meal-planning, improved sleep habits and reduced access to fast food when staying at home during movement restrictions 17 18. However, its worsening was observed in a small study from India (52 patients with type 1 diabetes)18 27 and in an early pandemic (April/May 2020) cross-sectional study in Brazil (1701 people with type 1 or 2 diabetes) 17 28.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, improvements in glycaemic control were seen in high-income countries during the pandemic, likely reflecting a high motivation for diabetes self-management due to associations with COVID-19 outcomes, supportive care through teleconsultations, and easier meal-planning, improved sleep habits and reduced access to fast food when staying at home during movement restrictions 17 18. However, its worsening was observed in a small study from India (52 patients with type 1 diabetes)18 27 and in an early pandemic (April/May 2020) cross-sectional study in Brazil (1701 people with type 1 or 2 diabetes) 17 28. In India, disruptions to healthcare access (non-availability of insulin or glucose strips and financial difficulties) were named as underlying reason for deteriorations 18 27.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the COVID-19 pandemic has been reported to have no effect on glycated hemoglobin in diabetic patients, there is a relationship between decreased physical activity and increased glycated hemoglobin caused by telecommuting [ 16 ]. In fact, it has been reported that the amount of physical activity in diabetic patients is decreasing [ 17 ], and it is not certain what the long-term effects will be. Considering the disincentive for physical activity in the past and the social situation in recent years, to continuously correct postprandial hyperglycemia, we propose that exercise should be time-efficient and able to be performed anywhere.…”
Section: Introductionmentioning
confidence: 99%